The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/2175-7860200960311
|View full text |Cite
|
Sign up to set email alerts
|

Variação cambial em Serjania caracasana (Sapindaceae): enfoque na adequação terminológica

Abstract: RESUMO(Variação cambial em Serjania caracasana (Sapindaceae): enfoque na adequação terminológica) O corpus lignosum compositum, típico para as lianas da família Sapindaceae, é designado neste trabalho como "cilindro vascular composto". No caule de Serjania caracasana (Jacq.) Willd. essa variação cambial está representada por um cilindro vascular central circundado por oito cilindros vasculares periféricos. Não existe consenso quanto à terminologia que envolve essa estrutura, o que torna difícil uma abordagem a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 11 publications
5
19
0
3
Order By: Relevance
“…These similarities between the two organs have also been confirmed in more recent studies: phloem wedges in lianas of Bignoniaceae (Gabrielli, 1992;Martinelli et al, 2008;Victorio and Angyalossy, 2014) and successive cambia in the families Basellaceae, Nyctaginaceae, Menispermaceae and Aizoaceae (Carlquist, 1999(Carlquist, , 2004(Carlquist, , 2007Tamaio, 2006). For Sapindaceae, the object of this study, no cambial variants were found in the roots of the only species studied, Serjania caracasana (Tamaio, 2001), although the stem of this species and numerous others in this large Neotropical genus exhibits a conspicuous cambial variant known as compound vascular cylinder (Schenck, 1893;Solereder, 1908;Pfeiffer, 1926;Obaton, 1960;Van der Walt et al, 1973;Acevedo-Rodr ıguez, 1993;Tamaio and Angyalossy, 2009).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…These similarities between the two organs have also been confirmed in more recent studies: phloem wedges in lianas of Bignoniaceae (Gabrielli, 1992;Martinelli et al, 2008;Victorio and Angyalossy, 2014) and successive cambia in the families Basellaceae, Nyctaginaceae, Menispermaceae and Aizoaceae (Carlquist, 1999(Carlquist, , 2004(Carlquist, , 2007Tamaio, 2006). For Sapindaceae, the object of this study, no cambial variants were found in the roots of the only species studied, Serjania caracasana (Tamaio, 2001), although the stem of this species and numerous others in this large Neotropical genus exhibits a conspicuous cambial variant known as compound vascular cylinder (Schenck, 1893;Solereder, 1908;Pfeiffer, 1926;Obaton, 1960;Van der Walt et al, 1973;Acevedo-Rodr ıguez, 1993;Tamaio and Angyalossy, 2009).…”
Section: Introductionmentioning
confidence: 91%
“…Sections were made with a sliding microtome, double-stained in astra blue and safranin (Bukatsch, 1972, modified by Kraus and Arduin, 1997) and mounted in Canada balsam to make permanent slides. (1893), Solereder (1908), Pfeiffer (1926), Obaton (1960), Van der Walt et al (1973), Acevedo-Rodr ıguez (1993), Ara ujo and Costa (2006), Tamaio andAngyalossy (2009), Tamaio andSomner (2010), Borniego and Cabanillas (2014) and Bastos (2015).…”
Section: Anatomical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Carlquist (2001) não considera como variação cambial, e sim como uma característica que ocorre no hábito escalador, sendo restrita a poucas famílias arbóreas (IAWA Committee, 1989). Esse tecido é mencionado para plantas suculentas, como Crassulaceae (Metcalfe & Chalk, 1950), plantas que habitam regiões áridas, como Brassicaceae, Asteraceae e Cactaceae (Metcalfe & Chalk, 1950;Soffiatti, 2003) e plantas escaladoras (Dias-Leme, 1999;Tamaio, 2001;Ozório-Filho, 2002 .…”
Section: Comprimento Dos Elementos De Vasosunclassified